Challenges in the public procurement of PPE in federal hospitals in Rio de Janeiro / Brazil during COVID-19 (Revista Contexto & Saúde, 2025)
This study mapped hurdles and strategies in public procurement of Personal Protective Equipment (PPE), through a descriptive approach involving self-completion of an electronic survey instrument by personnel with purchasing experience from federal public hospitals. The instrument covered the supply process: general characteristics, common problems, and strategies necessary to overcome difficulties in the procurement process of seven selected PPEs (avental, máscara cirúrgica, máscara respiradora PFF2 ou N95, touca, protetor facial, óculos de proteção e sapatilha). We observed recurring procurement processes undertaken without tendering, in accordance to urgently-passed legislation by the Brazilian government, that waivered this obligation. High prices of PPEs and market shortages were the most usual problems, cited by over 80% of the respondents, especially for disposable surgical aprons and masks, and for filtering facepiece respirators (FFR) such as FFP2, and N95. Surge in demand associated with a disruption in global supply contributed to abusive prices. Negotiations with bidders, exchange of information between buyers and the search for alternative suppliers were the most important measures taken to tackle procurement problems. Difficulties in PPE procurement are a consequence of supply chain inadequacies as well as deficiencies in productive capacity in Brazil and worldwide. The mitigating actions employed in the face of procurement problems show the resilience of procurement systems.
Keywords: Personal Protective Equipment; Public Procurement; Legislation; Unified Health System; COVID-19